FAECAL GLUCOCORTICOID MEASUREMENT AS INDICATOR STRESS IN WILD CRESTED MACAQUES (MACACA NIGRA): THE IMPORTANCE OF VALIDATION AND SAMPLE PROCESSING TECHNIQUES - . Gholib; Taufiq P. Nugraha; Muhammad Agil; Iman Supriatna; Bambang Purwantara; Antje Engelhardt (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2014)
Monitoring of physiological stress in wild and/or endangered animals living in their natural habitat can be generated via measuring faecal glucocorticoid metabolites (FGCMs) through enzyme immunoassay technique. However, a careful validation of each enzyme immunoassays (EIAs) and methodological issues such as samples preservation, and extraction procedures must be a significant concern and validated because  it may influence FGCMs levels. In this present study, the aim was to carry out a biological validation to find reliable EIAs that could be used for non-invasive measurement of glucocorticoid levels in crested macaques. Moreover, we compared three different techniques of preservation: lyophilisation, oven drying and field extraction and three different solvents for extraction: 80% methanol, 90% pure ethanol and 90% commercial alcohol (isopropyl alcohol) to find the simple and practical techniques for sample processing. For hormone analysis, we colIected 189 faecal samples from wild crested macaques living in the Tangkoko-Batuangus Nature Reserve, North Sulawesi, Indonesia. The results show that biological validation can be used to validate measurement of faecal glucocorticoid which 3α,11β-dihydroxy-etiocholanolone was the most reliable EIAsfor this species. Different preservation and solvent extraction were not significantly influenced levels of FGCMs (p0.05). In conclusion, Our study highlights the importance of biological validation of FGCMassays and presents practical techniques for the non-invasive monitoring of physiological stress in crested macaques.